Racial Prejudice Towards African-American Portrayed In 12 Years A Slave - Nur Ida; Diyah Fitri Wulandari (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
Racial prejudice is a wrong assessment in society which is done by particular group towards other groups based on their visual appearance. These researches aimed to investigate the factors causing racial prejudice as depicted in 12 Years A Slave movie. The data were collected by using a qualitative method. This literary research examines the racial prejudice of white people towards black people. White people have negative prejudice towards black people without enough knowledge. The result of the research illustrated the racial prejudice arises because of two factors. They are Hereditary Categorical Thinking about Others and In-Group Superiority and Out-Group Discrimination Keywords: 12 Years a Slave, Racism, Racial Prejudice, Slave Narrative